Socioeconomic Challenges on Algeria’s Progress toward SDG2 (Zero Hunger): Public Spending, Agriculture, and Economic Resilience - Seyf Eddine Benbekhti; Mohammed Bouknadil; Hadjer Boulila; Ahmed Zeghoudi (SocioEconomic Challenges)
Ensuring food security and promoting sustainable agriculture are critical global priorities, particularly in Algeria, a country endowed with substantial agricultural potential yet challenged by resource inefficiencies, climate variability, and a heavy reliance on food imports. This paper investigates the role of sustainable agricultural practices in advancing Algeria's progress toward Sustainable Development Goal 2 (SDG 2: Zero Hunger), focusing on key factors influencing agricultural productivity and food security. Using a Vector Autoregressive (VAR) model, the study examines dynamic relationships between government agricultural expenditures, food production indices, and non-oil GDP growth over the period from 2010 to 2022. Algeria’s agricultural sector faces substantial structural and external barriers, such as insufficient water resource management, limited rural development initiatives, and the vulnerabilities imposed by climate change, which exacerbate the country’s dependence on food imports to meet growing domestic demand. The findings reveal that increased government spending on agriculture has a statistically significant and positive impact on agricultural productivity and food security in the short term. However, the long-term benefits of such expenditures diminish without consistent investment and the implementation of adaptive measures. Furthermore, non-oil GDP growth has a varying impact on food security, underscoring the need for economic diversification to enhance resilience within the agricultural sector. The study also highlights the importance of targeted investments in agricultural infrastructure, sustainable water resource management, and integrated rural development to achieve lasting food security and sustainability. By addressing these issues, Algeria can unlock its agricultural potential, reduce dependency on imports, and ensure a more sustainable and self-reliant future. The study provides actionable insights for policymakers, development organizations, and stakeholders aiming to improve food security and promote sustainable agricultural practices, offering a comprehensive roadmap for achieving long-term agricultural and economic sustainability.